Pengaruh Digital Marketing dan Electronic Word of Mouth (E-WOM) terhadap Minat Beli Generasi Z - Annisa Fadhillah Sukma; Nonika Dewi Shadrina (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
The development of digital technology has changed consumer behavior patterns, especially among Generation Z, who grew up as digital natives and are highly active on social media. This study aims to analyze the effect of Digital Marketing and Electronic Word of Mouth (E-WOM) on Generation Z Consumers' Purchase Intention, both partially and simultaneously, given the inconsistent findings of prior studies regarding these two variables. This research applies a quantitative associative approach using Partial Least Square Structural Equation Modeling (SEM-PLS) with SmartPLS 4. The population consists of Generation Z consumers (born 1997–2012) who have been exposed to digital marketing and electronic reviews prior to purchasing, selected through purposive sampling, with data collected via an online questionnaire using a 5-point Likert scale. Results from 100 respondents show that Digital Marketing and E-WOM each have a positive and significant effect on Purchase Intention, both partially (β = 0.367 and β = 0.522; p < 0.05) and simultaneously (R² = 0.470; F = 42.935; p < 0.05), so all three hypotheses are supported. E-WOM shows a stronger effect than Digital Marketing. These findings reinforce digital marketing literature and provide practical contributions for businesses in designing Digital Marketing strategies and managing E-WOM effectively to increase Generation Z's purchase intention.